Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s10854-015-3281-z
|View full text |Cite
|
Sign up to set email alerts
|

Defect-dipole alignment and strain memory effect in poled Li doped (Bi0.5Na0.4K0.1)0.98Ce0.02TiO3 ceramics

Abstract: Asymmetric ferroelectric hysteresis (P-E) loops and strain hysteresis (S-E) curves are detected in poled-aged Li doped (Bi 0.5 Na 0.4 K 0.1 ) 0.98 Ce 0.02 TiO 3 ceramics at room temperature. Temperature dependence of electrical and structural analysis is used to study the stability of electrically induced long-range ferroelectric order. Interestingly, this asymmetric characteristic can sustain at 80°C B T B 90°C, where the ferroelectric and non-ergodic relaxor phase coexist. Our results suggest that the prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Instances of large asymmetric S-E loops have been experimentally reported in a range of ferroelectric materials [38]. In [39], the authors report a strain difference of 0.15% in Li doped (Bi 0.5 Na 0.4 K 0.1 ) 0.98 Ce 0.2 TiO 3 ceramics which they propose is due to alignment of (Li…”
Section: A Dopant-vacancy Concentrationmentioning
confidence: 91%
“…Instances of large asymmetric S-E loops have been experimentally reported in a range of ferroelectric materials [38]. In [39], the authors report a strain difference of 0.15% in Li doped (Bi 0.5 Na 0.4 K 0.1 ) 0.98 Ce 0.2 TiO 3 ceramics which they propose is due to alignment of (Li…”
Section: A Dopant-vacancy Concentrationmentioning
confidence: 91%
“…Shi et al reported a defect dipole induced by partial Li + entering the B site in Li-substituted (Bi 0.5 Na 0.4 K 0.1 ) 0.98 Ce 0.02 TiO 3 (Li, Ce-BNKT) in which the (Li Ti − V •• O ) will create an asymmetric shift of the hysteresis loop and the strain curve in the polarized FE phase region that causes a large strain memory effect. When the temperature is higher than the depolarization temperature within a certain range, although it has entered the ER phase, the hysteresis loop and strain still retain asymmetry, as displayed in Figure 8, as a result of the directional pinning action of defect dipoles in the remaining ferroelectric phase [85].…”
Section: Volume Effect Of Polarized Bnt-based Materialsmentioning
confidence: 99%
“…For example, the technique of co-doping at the A and B site of perovskite structure of BNKT ceramics with dopants such as Ta [253], Nb [254], Zr [255], Hf [256], Mn [257], Li [258], and La [259], etc reported improved piezoelectric and energy storage applications [72,[260][261][262]. Details of co-doped ferroelectric BNT-systems are also reported elsewhere [72,[260][261][262][263][264][265][266][267]. Similarly, the co-doped system of 0.96[{Bi 0.5 (Na 0.84 K 0.16 )} 1−x−y Li x Mg y (Ti 1−z Nb z ) 3 ] -0.04SrTiO 3 reported enhanced energy storage performance in a temperature range of 100 • C-150 • C, with an energy storage density of 0.70 J cm −3 at an electric field of 5.5 kV mm −1 [260].…”
Section: Co-doping At A-and B-sitesmentioning
confidence: 99%